Effect of pipeline-seabed gaps on the vertical forces of a pipeline induced by submarine slide impact. (1st February 2021) - Fan, Ning; Sahdi, Fauzan; Zhang, Wangcheng; Nian, Tingkai; Randolph, Mark F.
Abstract: In recent years, the interaction between submarine slide runout and offshore pipelines has received extensive attention, based on the need to protect pipelines crossing regions susceptible to submarine slides. The interaction force between the slide material and a pipeline may be resolved into horizontal and vertical components, but with most attention to date focusing on the former while the latter has not been studied thoroughly. This paper reports the results from a series of multiphase flow (slide material and the ambient seawater) numerical simulations using a computational fluid dynamics (CFD) approach aimed at investigating the vertical forces during submarine slide flow around a pipeline at different gap ratios (pipeline-seabed gap normalized by pipeline diameter) from 0.08 to 10.0 and at Reynolds numbers ranging from 0.38 to 267. The oscillatory characteristics and magnitude of the vertical forces for different gap ratios are discussed. The effects of the gap ratios on the geotechnical and inertial components of the slide-pipeline vertical forces are analyzed systematically using a hybrid geotechnical-fluid mechanics framework. From the results of the CFD simulations, a modified hybrid geotechnical-fluid mechanics method to estimate the slide-pipeline vertical forces is developed considering the effects of pipeline-seabed gaps. Highlights: The oscillatory characteristics and magnitude of the submarine slide-pipeline vertical forces for different pipeline-seabed gaps are discussed from a series of multiphase flow numerical simulations using a computational fluid dynamics approach. The effects of the pipeline-seabed gaps on the geotechnical and inertial components of the slide-pipeline vertical forces are analyzed systematically using the hybrid geotechnical-fluid mechanics framework. An extended hybrid geotechnical-fluid mechanics approach is proposed to estimate the submarine slide-pipeline vertical forces.